Methodological basis for the study of corruption problems (administrative dimension) - Румянцев, Юрій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The problem in the methodology of research in fighting corruption from the perspective of administrative law. Different approaches to research methodology corruption with current advances in philosophy, sociology and statistics. Forming copyright proposals to improvere search methodology corruption. In conditions of weak democratic traditions, imperfections National legislation and insufficient level of legal culture Of citizens, corruption has negative consequences for all layers Ukrainian society, demoralizes citizens and destroys their trust in State In developing state anti-corruption strategy and relevant Mechanisms to overcome corruption should be taken into account that this is a complex phenomenon. The causes of which are not so much in the imperfection of human behavior, as in Organization of power mechanisms. Despite the efforts made and some achievements in Ukraine There are still a number of reforms in the field of combating corruption. And get started Implement concrete measures to fight corruption is necessary from the local equal. Because, it is the bodies of local self-government that form the primary Corruption system of regulation of social relations, and is the basis for The spread of corruption within the entire state. Despite the large number of studies of economic, political,Legal and social factors contributing to the emergence of corruption is lackingWorks that directly address the problem of corruption in the bodies Local Government.Can not know The whole thing differently, as first to decompose it into separate elements, to find out Functions and interconnections, which in turn are conditioned by functioningThe system as a whole. This is the essence of the dialectic, which takes into account the contradictionKnowledge and is based on the principle of development, the method of convergence from Abstract, that is, underdeveloped, not filled with definitions, to Concrete, that is, developed, enriched by definitions. At the same time the move Abstract thinking corresponds to the actual state of things.When studying what constitutes the subject of research, great Values have such philosophical laws as the law of unity and struggle Opposites, the transition of quantitative changes to qualitative, negation of negation,As well as categories: causes and consequences, general, special and individual, Necessary and incidental, possibilities and reality, content and form, essence andPhenomena and so on. The research arsenal includes other general sciences. Methods which, in their totality, form the methodology of science, under which understand the system of certain the ories acting as a guiding principle, an instrument of scientific analysis, a means to implement the requirements of this analysis.